2013
DOI: 10.1371/journal.pone.0071684
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Consumption Disrupts the Core Molecular Clock and Diurnal Rhythms of Metabolic Genes in the Liver without Affecting the Suprachiasmatic Nucleus

Abstract: Chronic ethanol consumption disrupts several metabolic pathways including β-oxidation and lipid biosynthesis, facilitating the development of alcoholic fatty liver disease. Many of these same metabolic pathways are directly regulated by cell autonomous circadian clocks, and recent studies suggest that disruption of daily rhythms in metabolism contributes to multiple common cardiometabolic diseases (including non-alcoholic fatty liver disease). However, it is not known whether ethanol disrupts the core molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
103
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 54 publications
19
103
1
Order By: Relevance
“…Diurnal rhythms of blood glucose, lactic acid, and cholesterol were also shifted following chronic alcohol (Rajakrishnan et al, 1999). Last, changes in the expression of clock and clock-controlled genes in the liver have been observed after chronic alcohol (Farnell et al, 2008;Filiano et al, 2013;Zhou et al, 2014). In the present study, we found multiple changes in rhythms within the HPA axis after chronic alcohol.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Diurnal rhythms of blood glucose, lactic acid, and cholesterol were also shifted following chronic alcohol (Rajakrishnan et al, 1999). Last, changes in the expression of clock and clock-controlled genes in the liver have been observed after chronic alcohol (Farnell et al, 2008;Filiano et al, 2013;Zhou et al, 2014). In the present study, we found multiple changes in rhythms within the HPA axis after chronic alcohol.…”
Section: Discussionsupporting
confidence: 64%
“…Pituitary: Con, U = 229, p < 0.01; Alc, U = 242.5, p < 0.01. Adrenal: Con, U = 252.2, p < 0.01; Alc, U = 170, p < 0.1. report that chronic alcohol did not affect the molecular clock in the SCN (as measured by Per2 expression) while advancing clocks in the liver (Filiano et al, 2013). Other groups have reported alterations in the rhythmic expression of clock genes in the SCN after alcohol (Chen et al, 2004(Chen et al, , 2006Farnell et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Eight-week-old male C57BL/6J mice were purchased from Jackson Laboratories and allowed to acclimate for at least 1 wk before they were divided into control and ethanol feeding groups. For the feeding studies, each ethanol-fed mouse was weight-matched to a control-fed mouse partner to establish the pairfeeding regimen (13). Mice were singly housed in standard husbandry boxes with bedding and kept in a temperature-and humidity-controlled environment under a 12:12-h light-dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol treatment increased hepatic triglycerides in clock mutant mice more than in wildtype mice and altered lipogenic gene expression in clock mutant mouse liver (Kudo et al, 2009). The diurnal rhythm of many primary clock genes (Bmal1, Clock, Cry1/2, and Per1/2) and CCGs (Dbp, Npas2, and Rev-erba) were altered in alcohol-fed mouse livers (Filiano et al, 2013) and caused phase shifting of diurnal rhythm of hepatic triglycerides, cholesterol, and bile acid levels (Zhou et al, 2014). Alcohol also alters the NAD/ NADH ratio, which regulates sirtuin SIRT1 activity and downstream target genes Bmal1/Npas2/Clock (Nakahata et al, 2009).…”
Section: Circadian Rhythm In Metabolic Diseasesmentioning
confidence: 96%
“…The methylated/nonmethylated DNA ratios in CpG islands in the PGC-1a gene promoter in diabetic patients is correlated with serum insulin and a homeostasis model of assessment of insulin resistance. Chronic alcohol consumption disrupts clock genes and diurnal rhythms of liver metabolic genes (Filiano et al, 2013). However, the mechanism of ethanol effect on circadian clock expression is not clear.…”
Section: Circadian Rhythm In Metabolic Diseasesmentioning
confidence: 99%